Utilização de biomassa de pinhão manso como adsorvente para remoção de corante rosa de bengala de soluções aquosas - Barbosa, Éder de Freitas (2018)
In this study, it has been studied the potential of the use of Jatropha Curcas deoiled cake, an agroindustrial residue derived from biodiesel production chain, as an adsorbent to remove an anionic xanthene class dye, the rose bengal (RB) dye. It has been tested the natural deoiled cake and two of this biomass that received different types of heat treatments. The adsorbents were characterized by scanning electron microscopy (SEM), spectroscopy in the infrared region (FTIR), thermogravimetry (TG/DTG) and elemental analysis, and it was possible to verify some changes in these materials after the heat treatments. The adsorbent mass, dye concentration and pH parameters caused significant effects on the efficiency of the adsorptive processes analysed and were optimized by Surface Response Methodology (SRM). The maximum adsorption capacity was obtained by the natural biomass, corresponding to 344 mg g -1 . The kinetic data were better adjusted to the pseudo -second order model. The adjustment of the experimental data to the isotherm models revealed that the Sips model was more adequated. The thermodynamic studies indicated that the adsorption processess were endotermic and favorable for all three biomass. The reuse tests showed that the biomass can be regenerated with reasonable efficiency by dessorption using heated water. However, the dessorption efficiency decreased over the cycles or the adsorbents lost mass, probably by solubilization in water.